2015
DOI: 10.1016/j.micromeso.2014.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Elastic behavior and pressure-induced structural modifications of the microporous Ca(VO)Si4O10·4H2O dimorphs cavansite and pentagonite

Abstract: The behavior of natural microporous cavansite and pentagonite, orthorhombic dimorphs of Ca(VO)(Si 4 O 10 )•4H 2 O, was studied at high pressure by means of in situ synchrotron X-ray powder diffraction with a diamond anvil cell using two different pressure-transmitting fluids: methanol:ethanol:water = 16:3:1 (m.e.w.) and silicone oil (s.o.). In situ diffraction-data on a cavansite sample were collected up to 8.17(5) GPa in m.e.w, and up to 7.28(5) GPa in s.o.The high-pressure structure evolution was studied on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
5
4
0
Order By: Relevance
“…Variations in unit cell of Pentagonite are relatively monotonous. This observation is consistent with the experimental finding by Danisi et al [27] (see Figure 5) who have noted similar anisotropic compressibility along the b axis only for Cavansite.…”
Section: Pressure-dependent Abundancesupporting
confidence: 93%
See 2 more Smart Citations
“…Variations in unit cell of Pentagonite are relatively monotonous. This observation is consistent with the experimental finding by Danisi et al [27] (see Figure 5) who have noted similar anisotropic compressibility along the b axis only for Cavansite.…”
Section: Pressure-dependent Abundancesupporting
confidence: 93%
“…From these data, we obtain estimated bulk modulii of 33.7GPa and 41.1GPa for Cavansite and Pentagonite respectively. These numbers are in excellent agreement with those observed experimentally (38 GPa and 49 GPa respectively) [27]. Importantly, for all positive pressures, Cavansite remains lower in energy (hence favored).…”
Section: Pressure-dependent Abundancesupporting
confidence: 91%
See 1 more Smart Citation
“…Above 550 K the transient cell-expanding effect has ended and the framework proceeds to an progressive squashing of eight-ring channels assisted by the counter-rotations around the 4MR-O5-4MR hinges. A similar behaviour was also observed in cavansite under high-pressure conditions (Danisi et al, 2015) when the T-O-T angles antirotate while the V-O-T angles corotate when the volume decrease. We found that the extreme collapse of the elliptical apertures leaving just 1.5 Å a minimum free diameter, along with the reduced Ca coordination in agreement with Danisi et al (2012), leads to the amorphization of cavansite.…”
Section: Discussionsupporting
confidence: 77%
“…The response to heating of cavansite has been investigated by TG/DTA methods (Ishida et al 2009 and reference therein), laboratory HT powder diffraction without Rietveld analysis (Ishida et al 2009), ex-situ (Rinaldi et al 1975) and in situ (Danisi et al 2012) single crystal diffraction, in-situ FTIR and Raman spectroscopy (Prasad and Prasad 2007). The high-pressure behaviour has also been studied by Danisi et al (2015). Rinaldi et al (1975) determined the crystal structure of partly dehydrated cavansite from Oregon, U.S.A by ex situ single crystal XRD.…”
Section: Introductionmentioning
confidence: 99%